Effect of Salinity Difference and Fertilizer Dose Walne against Chlorella sp Population Growth in Laboratory Scale - Fathiya Hanifa; Syafruddin Nasution; Sofyan Husein Siregar (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstrakChlorella sp is a single-celled plants that have a true nucleus, and relatively low-level plants. Chlorella sp also called the green algae and can live in freshwater and sea water. This research was conducted in January-February 2019, which is housed at the Institute of Aquaculture Seawater and Brackish Bungus Buo bay, Padang, West Sumatra. The purpose of this study to determine the effect of the combination of salinity and Walne different fertilizers on the growth of Chlorella sp population on a laboratory scale. result This study shows that salinity combinations and dosages of different Walne influence on population growth Chlorella sp, The rate of growth (k) is the highest at the beginning of the growth that is the treatment with the growth rate (k) of 0.84 cells / hour. Relative growth rate of Chlorella sp showed increased growth in a relatively unstable. Specific growth rate that occurred during the growth phase showed that the population growth of Chlorella sp longest namely the treatment of A1B1 which the growth rate up to the 12th day. Keywords:Chlorella sp, Walne fertilizer, combination, salinity.